Space Syntax in Adjustment of Space Patterns of Sofbol Stadions in Surabaya - Heristama Anugerah Putra; Prabani Setio Hastorahmanto (Center for Scientific Publication, 2023)
Stadiums generally have a lot of access for entrances and exits, this is related to the spectator capacity of the stadium which is quite a lot. The level of ease of user activity with the existing spatial configuration structure is unknown. The adjustment of the softball stadium plan is intended to provide a level of clarity in the pattern of relationships between spaces and a level of ease of accessibility in achieving these spaces. Apart from that, it is also to know and understand the basic movement patterns of users in it. So that the space syntax analysis method is used to find out clarity regarding the pattern of configuration of relationships between spaces in the ease of outreach of activities for users in the stadium. Analysis related to connectivity, integrity and intelligibility patterns can in a descriptive way provide the appropriate picture results in the form of an axial line. The expected result is that the pattern of relationships between spaces for ease of user activity in them feels very far-reaching, especially on the 1st to 3rd floors. There needs to be a clear link on these floors to understand the spatial configuration structure for the users inside. While the floor that has the most optimal quality with an intelligibility value close to 1 is floor 4, where on this floor the range of activities is quite close together and not too wide.